PENGARUH CORPORATE GOVERNANCE DAN DEFERRED TAX EXPENSE TERHADAP EARNINGS MANAGEMENT PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - Sri Suranta; Rendi Rendi (Jurnal Akuntansi, 2017)
This study aims to find out the effect of corporate governance and deferred tax expense toward earnings management in Indonesia. Corporate governance represented by board of commissioner, independent commissioner, institutional ownership, and female commissioner. Sample in this study consists of 100 manufacturing companies in 2013 and 2014. Sample is taken using the purposive sampling method. Regression results show that institutional ownership, and deferred tax expense are influencing the earnings management, while the board of commissioner, independent commissioner and female comissioner are not. Keywords: corporate governance, deferred tax expense, earnings management